Dietary supplementation with a designer metabolic modulator improves MASLD and associated anxiety in mice - Segala, Agnese; Favero, Gaia; Bottani, Emanuela; Vetturi, Alice; Garrafa, Emirena; Parrella, Edoardo; Ruocco, Chiara; Ragni, Maurizio; Rezzani, Rita; Nisoli, Enzo; Valerio, Alessandra (Frontiers in Pharmacology, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD), is a multifaceted condition characterized by excessive liver fat accumulation associated with obesity or other risk factors. Patients with obesity-related MASLD often suffer from comorbid psychiatric conditions, including anxiety. The therapeutic approach for MASLD relies on weight management through dietary and behavioral modifications. Nutritional interventions with essential amino acids (EAAs) have emerged as safe and promising tools in treating metabolic disorders and liver diseases. This study aimed to investigate the effects of dietary supplementation with α5, a designer EAA-based metabolic modulator enriched with tricarboxylic acid cycle intermediates, in a murine model of diet-induced MASLD with associated anxiety.MethodsTen-week-old male C57BL/6J mice were fed for 17 weeks either a high-fat, high-sugar diet or a standard purified diet. The α5 compound (1.5 mg/g/day in drinking water) was administered to half of the mice fed each diet (n = 8/group). Mice body weight and energy intake were recorded. Liver and adipose tissue depot weights were calculated as ratios to body weight. Blood analytes were evaluated. Liver samples were analyzed for the enzymatic activity of mitochondrial chain respiratory complexes, gene expression (reverse transcription-qPCR), and histological features (hematoxylin-eosin and Masson’s trichrome staining). Liver disease severity was graded using the NAFLD Activity Score. The open field behavioral test was conducted to assess anxiety.ResultsMice fed the high-fat, high-sugar diet developed obesity, a MASLD phenotype, and anxiety-like behaviors. Dietary supplementation with α5 ameliorated liver pathology, including reduced hepatocellular ballooning, fat lipid droplet diameter, and the expression of genes related to fibrosis, without affecting body weight. Moreover, α5 supplementation significantly reduced the anxiety-like behavior observed in untreated MASLD mice.DiscussionThese results suggest that α5 represents a novel intervention to prevent or mitigate the progression of MASLD and its associated mental health complications.